Optical and electrical properties of tellurite base glass added with bismuth and holmium oxides - Oo, Hooi Ming (2013)
Tellurite glasses are good material in non-linear, photonic and communication application because these glasses are stable and provide low photon energy in room temperature. When other metal oxides are added in the tellurite glass system, it can enhance the optical and electrical behaviour. For this research, two series of binary tellurite based glasses: bismuth and holmium tellurite were successfully synthesized using a conventional melt quenching method. XRD results for both binary tellurite glass system show that the glasses are in amorphous phase. The glass samples are transparency, yellow colour for bismuth tellurite glass, orange colour holmium tellurite glass when there is no sunlight and yellow colour when sunlight is present. The optical and electrical properties measurements were investigated for both binary tellurite glasses system. For bismuth tellurite glass system, the density, molar volume and refractive index increase when bismuth ions Bi3+ increases. This is due to the increase in the polarization of the ions Bi3+. FTIR results show that it slightly shifted to the low wavenumber and this due to formation of TeO3 units and non-bridging oxygen. When formation TeO3 units and non-bridging oxygen increase, the optical band gap, Eopt decreases. The conductivity and the resistance in electric properties depend on the network modifier present in the sample. As ion Bi3+ content increases, the formation of non-bridging oxygen in the sample increase leads to an increase in the conductivity of the sample. For holmium tellurite glasses, as the holmium content increases, the density increasing while the molar volume decreases. Besides, the refractive index increases when the holmium content increases. FTIR results show that it slightly shifted to the low wave number and this also due to formation of TeO3 units and non-bridging oxygen. For electrical properties, the increase of ion Ho3+ content will increase the formation of holmium (iii) oxide quasi-molecular complexes in tellurite glass matrix which causes the conductivity of the sample to decrease.